Existence and uniqueness of continuous solutions of nonlinear functional equations are generic properties - Jarczyk, Witold (Annales Mathematicae Silesianae, 1990)
Fundamental properties of equations of the form (1) are discussed from the Baire category point of view. After showing that they are generic in a suitable function space the density of the set of equations (1) having no solutions is studied. Results of the paper are “product versions” of these proved in [3].